ROMANTIC ELEMENTS IN JOHN KEATS’ POEM ODE TO A NIGHTINGALE - Rizky, Nur Isni; Manugeren, M (Universitas Islam Sumatera Utara, 2025)
Ode to a Nightingale, composed in the spring of 1819, is widely regarded as one of John Keats' most profound poetic achievements. Inspired by the spontaneous experience of hearing a nightingale's song, the poem presents a speaker who, while immersed in an imagined forest, engages in deep reflection on the themes of beauty, mortality, temporality, nature, and human suffering. The nightingale functions not merely as a bird, but as a symbol of transcendent beauty and imaginative escape from the harsh realities of life. This study examines the Romantic elements embedded in the poem—namely Nature, Supernaturalism, Contemplation, Beauty, and Love—by employing an intrinsic literary approach as formulated by Wellek and Warren. Utilizing a descriptive qualitative method, as outlined by Creswell, this research focuses on textual analysis to uncover how these Romantic features are interwoven into the fabric of the poem. The findings underscore how Ode to a Nightingale not only exemplifies Romantic ideals but also reflects broader social and existential concerns, affirming literature's role as a mirror of human experience.